Research Trends on Augmented Reality Integration in Biology Learning: A Bibliometric Analysis (2015–2024) - Febby Apriani; Nabila Khaerunnisa; Erma Fitriyana (Indonesian Journal of Applied Science and Technology, 2025)
The development of educational technology has encouraged the use of Augmented Reality (AR) in biology learning to help visualize abstract and complex concepts. This study aims to analyze research trends related to the integration of Augmented Reality (AR) in biology learning during the period 2015–2024 using a bibliometric analysis approach. Publication data were obtained from Scopus, Web of Science, and Google Scholar databases. The data were analyzed to identify publication growth, author contributions, and dominant research topics. The results indicate a significant increase in publications, with dominant topics including anatomical visualization, cell structure, human organ systems, and AR-based interactive learning media. These findings suggest that AR has strong potential to support more interactive and effective innovations in biology education.